Usefulness of (18)F-FDG PET/CT for the Evaluation of Bone Marrow Involvement in Patients with High-Grade Non-Hodgkin’s Lymphoma - Lee, Yukyung (Springer-Verlag, 2012)
PURPOSE: To assess the usefulness of (18)F-fluorodeoxyglucose PET/CT in the detection of bone marrow (BM) involvement of high-grade non-Hodgkin’s lymphoma (NHL). METHODS: One hundred twenty patients with newly diagnosed diffuse large B-cell lymphoma or peripheral T-cell lymphoma between January 2007 and June 2011, who received BM trephine biopsy and (18)F-FDG PET/CT before chemotherapy, were included in this retrospective study. We reviewed their (18)F-FDG PET/CT images and bone marrow biopsy (BMB) results. After reviewing the images, we reviewed the medical records and radiological findings of interesting patients. RESULTS: There were 23 (18)F-FDG PET/CT scans in which the marrow was considered to be abnormal (either positive or equivocal), and 97 (18)F-FDG PET/CT scans were regarded as having negative FDG uptake. Of 120 patients, 100 (83.3 %) had a concordant result of BM interpretation between (18)F-FDG PET/CT and BMB, and the remaining 20 patients had discordant results. Among 23 patients with either positive or equivocal (18)F-FDG PET/CT scans, 1 of 12 patients with ‘positive’ (18)F-FDG PET/CT had a lymphomatous involvement on BMB. In contrast, 10 of 11 patients with ‘equivocal’ BM hypermetabolism were reported as having positive involvement by BMB. Patients with abnormal (18)F-FDG PET/CT had significantly higher mSUV(highest) than those with normal FDG-PET/CT. CONCLUSIONS: (18)F-FDG PET/CT and BMB are complementary techniques in assessing the presence of BM involvement in patients with high-grade NHL. The increasing availability of (18)F-FDG PET/CT will raise the need for additional biopsy for FDG-avid lesions, especially in patients with negative standard BMBs. (18)F-FDG PET/CT can be useful as a decision-making tool for determining whether to perform a standard BMB or targeted biopsy to the FDG-avid lesion as an initial staging procedure. A direct bone biopsy for FDGpositive bone lesions should be included in staging guidelines in future. In (18)F-FDG PET/CT-negative cases, BMB is still a powerful procedure, but BMB alone is insufficient for full evaluation of BM.